Zinc Protects Human Kidney Cells from Depleted Uranium‐induced Apoptosis. (11th December 2013) - Hao, Yuhui; Ren, Jiong; Liu, Cong; Li, Hong; Liu, Jing; Yang, Zhangyou; Li, Rong; Su, Yongping
Abstract Depleted uranium (DU) is a weak radioactive heavy metal, and zinc (Zn) is an effective antidote to heavy metal poisoning. However, the effect of Zn on DU‐induced cytotoxicity and apoptosis is not completely understood. The purpose of this study was to evaluate the effect of Zn on DU‐induced cell apoptosis in human kidney cells (HK‐2) and explore its molecular mechanism. Pre‐treatment with Zn significantly inhibited DU‐induced apoptosis. It reduced the formation of reactive oxygen species in the cells, increased the catalase (CAT) and glutathione (GSH) concentrations, suppressed the DU‐induced soluble Fas receptor (sFasR) and soluble Fas ligand (sFasL) overexpression, suppressed the release of cytochrome c and apoptosis inhibitor factor (AIF) from mitochondria to cytoplasm, inhibited the activation of caspase‐9, caspase‐8 and caspase‐3, and induced metallothionein (MT) expression. Furthermore, exogenous MT effectively inhibited DU‐induced cell apoptosis. In conclusion, mitochondrial and FasR‐mediated apoptosis pathways contribute to DU‐induced apoptosis in HK‐2 cells. Through independent mechanisms, such as indirect antioxidant effects, inhibition of the activation of caspase‐9, caspase‐8 and caspase‐3, and induction of MT expression, Zn inhibits DU‐induced apoptosis.